Assessing the Quality of Milk Using a Multicomponent Analytical Platform MicroNIR/Chemometric - Risoluti, Roberta; Gullifa, Giuseppina; Materazi, Stefano (Frontiers in Chemistry, 2020)
In this work, an innovative screening platform based on MicroNIR and chemometrics is proposed for the on site and contactless monitoring of the quality of milk by a simultaneous multicomponent analysis. The novelty of this completely automated tool, consists of a miniaturized NIR spectrometer operating in a wireless mode that permits to process samples in a rapid and accurate way and to obtain in a single click a comprehensive characterization of the chemical composition of milk. To optimize the platform, milk specimens with a different origin and composition were considered and prediction models were developed by chemometric analysis of the NIR spectra using Partial Least Square regression algorithms. Once calibrated, the platform was used to predict samples acquired in the market and validation was performed by comparing results of the novel platform with those obtained from the chromatographic analysis.Results demonstrated the ability of the platform to differentiate milk as a function of the distribution of fatty acids, providing a rapid and non destructive method to assess the quality of milk and to avoid food adulteration.